NANOTECHNOLOGIES IN CHEMISTRY: INCREASING THE QUALIFICATIONS OF TEACHERS, ELECTIVE COURSES, METHODOLOGICAL IDEAS, ASSIGNMENTS AND CONTENT FORMATION - Malyshev, Viktor; Voitsekhivskyi , Mykhailo; Gab , Angelina; Lukashenko , Tetiana; Boichenko , Valentyn (Continuing Professional Education: Theory and Practice, 2023)
The essential importance of the psychological and professional training of the young generation and the adaptation of society to the tasks and problems of the use of nanotechnology is shown. It was noted that an important way to modernize education is the introduction of a system of specialized training in secondary schools, which involves taking into account the educational needs, inclinations and abilities of students, creating conditions for professional self-determination. Ways of differentiating education are shown. The importance and necessity of improving the qualifications of teachers of general education natural sciences as a necessary step for the introduction of elective courses was noted. Examples of topics related to the methodical training of teachers in the fields of nanophysics, nanochemistry, and nanobiology are given. The content and methodological ideas of the elective course «Modern Nanochemistry» are presented. The purpose, tasks and requirements for the mastery level of this course are highlighted. The results of the course should be the acquisition of knowledge on the basics of nanotechnology and nanochemistry, the main principles and achievements of nanochemistry, methods of its research, unique properties of nanomaterials, their application and prospects for the development of nanochemistry, the role of nanochemistry in solving common human problems. Appropriate criteria are proposed for evaluating the implementation of the course program. Students are expected to conduct scientific research, prepare essays and multimedia presentations. The proposed elective course consists of invariant and variable parts. The approximate content of the course includes seven most important topics. It is envisaged that students will carry out project activities as a method of increasing interest and holistic study of school subjects. Resource support for the course «Modern nanotechnological chemistry» was recommended, which includes recommended educational and methodological literature, Internet resources, and national periodicals on nanotechnology.